Structure–Affinity Relationships and Structure–Kinetics Relationships of Pyrido[2,1-f]purine-2,4-dione Derivatives as Human Adenosine A(3) Receptor Antagonists - Xia, Lizi (J Med Chem, 2017)
[Image: see text] We expanded on a series of pyrido[2,1-f]purine-2,4-dione derivatives as human adenosine A(3) receptor (hA(3)R) antagonists to determine their kinetic profiles and affinities. Many compounds showed high affinities and a diverse range of kinetic profiles. We found hA(3)R antagonists with very short residence time (RT) at the receptor (2.2 min for 5) and much longer RTs (e.g., 376 min for 27 or 391 min for 31). Two representative antagonists (5 and 27) were tested in [(35)S]GTPγS binding assays, and their RTs appeared correlated to their (in)surmountable antagonism. From a k(on)–k(off)–K(D) kinetic map, we divided the antagonists into three subgroups, providing a possible direction for the further development of hA(3)R antagonists. Additionally, we performed a computational modeling study that sheds light on the crucial receptor interactions, dictating the compounds’ binding kinetics. Knowledge of target binding kinetics appears useful for developing and triaging new hA(3)R antagonists in the early phase of drug discovery.